Uji Aktivitas Analgesik Campuran Ekstrak Kencur (Kaempferia Galanga) Dengan Kondroitin Dan Glukosamin Secara In Vivo Pada Mencit Putih (Mus Musculus) - Salsabila Aprilia Rizqi, '- (2021)
This study aims to determine the increase in analgesic activity of a mixture of 70 % ethanol extract of Kaempferia galanga rhizome with chondroitin and glucosamine in vivo. This study used writhing test as a method to determine its analgesic activity in mice (Mus musculus). Wriggling movements in mice were used as a parameter of the presence of pain. This study was an in vivo experimental study that uses sample of 28 healthy male Balb/c mice (Mus musculus). The sample was randomized into 7 groups. The first groups was given sodium CMC as negative control, the second groups was given aspirin 65 mg/kg BW as positive control, the third until fifth groups received a mixture of 70 % ethanol extract of Kaempferia galanga rhizome with chondroitin 52 mg/kg BW and glucosamine 65 mg/kg BW in the dose of 70 % ethanol extract of Kaempferia galanga rhizome respectively 840, 1.260 and 1.680 mg/kg BW, the sixth groups was given ethanol 70 % extract of Kaempferia galanga in dose 1.260 mg/kg BW and the seventh groups was given chondroitin 52 mg/kg BW and glucosamine 65 mg/kg BW. All interventions were administered by oral route. The result showed that the analgesic effect of a mixture of 70% ethanol extract of Kaempferia galanga rhizome with chondroitin and glucosamine was significantly different with negative control group (P<0,05) and the a mixture of 70 % ethanol extract of Kaempferia galanga rhizome in dose 1.680 mg/kg BW with chondroitin 52 mg/kg BW and glucosamine 65 mg/kg BW can increase analgesic activity in vivo as indicated by a significant difference in the frequency of stretching compared to aspirin at a dose of 65 mg/kgBW. From the result, it can be concluded that the administration of a mixture of 70 % ethanol extract of Kaempferia galanga rhizome at a dose of 1.260 and 1.680 mg/kg BW with glucosamine 65 mg/kgBW and chondroitin 52 mg/kgBW can increase the analgesic activity in vivo.